Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China - Wu, Chao; Liu, Chunxiang (Zootaxa, 2018)
Three species of the leaf-mimicking Tettigoniidae, Leptoderes Serville, 1838 were reported in the southeast of Asia. Here, we redescribe the type species L. ornatipennis Serville, and describe two new species Leptoderes shuzhenae sp. nov. and L. dianensis sp. nov., respectively from Tibet and Yunnan, China. Leptoderes now comprises five species. Informative illustrations are provided. The distribution of the Leptoderes Serville species is discussed and mapped. The holotypes are deposited in Insect Collection of Institute of Zoology, Chinese Academy of Sciences, Beijing, China (IZCAS).